(untitled) (Journal of Pharmaceutical Negative Results, 2022)
The medial end of the lesser wing of sphenoid forms the anterior clinoid process which gives attachment to tentorium cerebelli, it issometimes joined with the middle clinoid process with a spicule of bone and forms carotidoclinoid foramen. This study is done to obtainthe knowledge of morphometry of the anterior clinoid process which is important for neurosurgeons in approaching the lesions of thisarea.The length of ACP, the width of ACP, and the distance of ACP from its tip to OS were measured from the right and left sides of 31skulls( out of which 25 were males and 6 were females) using digital calipers.In the case of the male’s length in left side is more than the right side with p<0.001, Where as width does not differ between the leftand right sides with p>0.05, Distance between ACP & OS was more significant than the right side with p-value p<0.001. presence ofcarotid clinoid foramen was observed out of 11 carotido clinoid foramen( N=9 )were of incomplete form(most common), (N=1) contactform and( N=1)was of complete form.The knowledge of the morphology of ACP & CCF allows better surgical results and minimizes surgical morbidity.